2010
DOI: 10.1007/s00038-010-0154-3
|View full text |Cite
|
Sign up to set email alerts
|

Income or living standard and health in Germany: different ways of measurement of relative poverty with regard to self-rated health

Abstract: Our results challenge conventional measurements of the relationship between poverty and health that probably has been underestimated by income measures so far.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
12

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 65 publications
(102 reference statements)
0
25
0
12
Order By: Relevance
“…Unlike income, the standard of living measures periods of persistent income poverty and socioeconomic deprivation 59–61. A certain standard of living requires longer periods of financial investments, while the loss of standard of living requires longer periods of financial shortages 17 59 61 62. In addition, several factors, such as property ownership, age, education, employment and marital status, further contribute to individual's living standard 59 61.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike income, the standard of living measures periods of persistent income poverty and socioeconomic deprivation 59–61. A certain standard of living requires longer periods of financial investments, while the loss of standard of living requires longer periods of financial shortages 17 59 61 62. In addition, several factors, such as property ownership, age, education, employment and marital status, further contribute to individual's living standard 59 61.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research found that the standard of living is a robust social determinant of individual health 6 13–19. For example, Pfoertner et al 17 found in data from the German Socio-Economic Panel (GSOEP) that differences in material standard of living resulted in larger inequalities in self-rated health (SRH) than differences in income, education or occupational status. Other studies found similar results and suggest that the lack of a minimum level of living standard involves long periods of financial shortages 14 16.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Basic needs such as food, shelter and sanitation are frequently unmet (Pfoertner, 2011), all of which increase IDU’ susceptibility to poor health. In the present study, levels of unstable housing were high with more than 50% of the participants in the high income category reporting unstable housing.…”
Section: Discussionmentioning
confidence: 99%
“…For example, having a higher income enables better nutrition, exercise, housing, health care, and recreation (Marmot, 2002). Conversely, poverty has a strong deleterious effect on health and is associated with a cornucopia of unhealthy behaviours (Laaksonen et al, 2003; Pfoertner et al, 2011). In particular, low income has been observed to be significantly associated with the consumption of unhealthy goods, such as tobacco, alcohol and illicit drugs (Cerda et al, 2011; Jefferis et al, 2007; Redonnet et al, 2012).…”
Section: Introductionmentioning
confidence: 99%